The RNA helicase DHH1 is central to the correct expression of many developmentally regulated mRNAs in trypanosomes - Kramer, Susanne; Araújo de Queiroz, Rafael; Ellis, Louise; Hoheisel, Jörg D.; Clayton, Christine; Carrington, Mark (Journal of cell science, 2010)
In trypanosomes, the predominant mechanisms of regulation of gene expression are post-transcriptional. The DEAD-box RNA helicase DHH1 was identified in a screen for gene products that are necessary for the instability of the GPI-PLC mRNA in insect-stage trypanosomes. Expression of an ATPase-deficient dhh1 mutant caused a rapid growth arrest associated with a decrease in polysomes, an increase in P-bodies and a slight decrease in average mRNA levels. However, the effect of dhh1 mutant expression on both turnover and translational repression of mRNAs was selective. Whereas there was little effect on the stability of constitutive mRNAs, the control of a large cohort of developmentally regulated mRNAs was reversed; many mRNAs normally downregulated in insect-stage trypanosomes were stabilized and many mRNAs normally upregulated decreased in level. One stabilised mRNA, ISG75, was characterised further. Despite the overall decrease in polysomes, the proportion of the ISG75 mRNA in polysomes was unchanged and the result was ISG75 protein accumulation. Our data show that specific mRNAs can escape DHH1-mediated translational repression. In trypanosomes, DHH1 has a selective role in determining the levels of developmentally regulated mRNAs.
Gesehen am 23.03.2023